EFISIENSI PENGGUNAAN PAKAN TAMBAHAN DENGAN KANDUNGAN PROTEIN YANG BERBEDA TERHADAP LAJU PERTUMBUHAN DAN SURVIVAL RATE PADA BENIH IKAN KERAPU BEBEK (CROMILEPTES ALTIVELIS): Efficiency Use Feed Supplement With Different Protein Content On Growth Rate And Survival Rate In Fry Of Grouper Duck Fish (Cromileptes altivelis) - Anggraeni, Pramudji Novita; Kurniawati, Kurniawati; Rahmawati, Aryani; Furkan, Al (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
The purpose of the study is to determine efficiency of the use of additional types of feed with different protein content on the growth rate and survival rate of the fry grouper duck fish (Cromileptes altivelis). The method used in this research is the method of experiment which is a method of research by conducting a series of field trials of activities to see the results that may indicate position or relationship between variables clause - observed variables (Abdullah et al, 1985). From the research results can be obtained results growth rate grouper duck fish seed is highest on P3 is 0.052 grams / day and was lowest for the P4 is equal to 0,023 grams / day. While the value of the highest survival rate was obtained in P3 which anchovy at 95% and lowest for the meat snails P2 is only 25%. But at this result meat snails can obtain results that exceed the growth rate of fish peperek. The value of feed efficiency in P3 with a protein content of 63% is the highest efficiency rate is 23.16% and the lowest at 15.37% efficiency found in P4 with a protein content of 34%.